Response evaluation of locoregional therapies in combined hepatocellular–cholangiocarcinoma and intrahepatic cholangiocarcinoma versus hepatocellular carcinoma: a propensity score matched study. Issue 2 (February 2022) - Mukund, A.; V. Srinivasan, S.; Rana, S.; Vijayaraghavan, R.; Patidar, Y.; Arora, V.; Jindal, A.; Choudhury, A.; Shasthry, S.M.; Sarin, S.K.
Abstract : AIM: To evaluate the response of locoregional therapy (LRT) on combined hepatocellular–cholangiocarcinoma (cHCC-CC) and intrahepatic cholangiocarcinoma (IHC) and compare their outcomes with propensity matched hepatocellular carcinoma (HCC) patients. MATERIALS AND METHODS: From January 2011 to July 2020, 13 patients with cHCC-CC (11 men, two women, median age 56 years) and 15 IHC patients (10 men, five women, median age 60 years) were compared with 101 HCC patients (79 men, 22 women, median age 60 years) after LRT. All tumours were proven histologically. Among the 13 cHCC-CC patients, 11 received transarterial chemoembolisation (TACE), one received microwave ablation (MWA) and one received TACE with radiofrequency ablation (RFA). Of 15 IHC patients, eight received TACE, five received RFA, and one received MWA, and one received TACE with RFA. Propensity score matching (PSM) was done with conditional logistic regression adjusted for age, type of LRT, tumour specific features and Child–Pugh score. RESULTS: After LRT, on univariate analysis an objective response was seen in 30% of cHCC-CC and 53% of IHC patients. PSM analysis demonstrated shorter progression-free survival (PFS; cHCC-CC versus HCC: 1.5 versus 7.5 months; IHC versus HCC: 6 versus 14 months, p< 0.05), overall survival (OS; cHCC-CC versus HCC: 12 versus 28 months; IHC versus HCC: 18 versus 34 months, p< 0.005), and poor objective response (cHCC-CC versus HCC: 25% versus 91%; IHC versus HCC: 58% versus 88%, p< 0.05) in cHCC-CC and IHC patients versus HCC patients. Hypovascular tumour, macrovascular invasion, and infiltrative appearance were independent prognostic factors for OS in IHC patients. CONCLUSION: cHCC-CC and IHC are aggressive tumours with a poor objective response, greater distant progression of the disease and shorter PFS and OS post LRT as compared to HCC. Highlights: cHCC-CC and IHC are aggressive hepatic tumors with poor objective response post LRT. It has a shorter progression free and overall survival after LRT as compared to HCC. Tumour vascularity is a key factor in predicting tumor response before LRT. TACE may be considered as a bridging therapy before surgery/liver transplantation.